2010
DOI: 10.1007/s12206-010-0704-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of a finite length euler-bernoulli beam on linear and nonlinear viscoelastic foundations to a concentrated moving force

Abstract: In this paper the dynamic response of a simply-supported, finite length Euler-Bernoulli beam with uniform cross-section resting on a linear and nonlinear viscoelastic foundation acted upon by a moving concentrated force is studied. The Galerkin method is utilized in order to solve the governing equations of motion. Results are compared with the finite element solution for the linear foundation model in order to validate the accuracy of the solution technique. A good agreement between the two solution technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…The maximum deflection will occur at the location of the load. Furthermore, excellent agreement of the present result and [19] for load velocity V = 50m/s is obtained. Figure 3 displays the comparison between the results of the analytical and Rayleigh-Ritz methods for selected load velocity V = 55m/s and for a beam extended 15 m in longitudinal direction.…”
Section: Numerical Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The maximum deflection will occur at the location of the load. Furthermore, excellent agreement of the present result and [19] for load velocity V = 50m/s is obtained. Figure 3 displays the comparison between the results of the analytical and Rayleigh-Ritz methods for selected load velocity V = 55m/s and for a beam extended 15 m in longitudinal direction.…”
Section: Numerical Resultssupporting
confidence: 85%
“…Steele [15] and Chen and Huang [16,17] investigated the response of Timoshenko beam on Winkler foundation for a variety of beam, foundation, and loading conditions. Yang and Ge [18] and Senalp et al [19] investigated the dynamic behavior of Euler-Bernoulli beam resting on viscoelastic foundation subjected to moving load by using the mode decomposition method together with the precise time integration method (MDPIM). Vlasov and Leont' ev [20] showed that the mechanical behavior of an elastic continuum can be quite accurately simulated using springs with shear interactions between them.…”
Section: Introductionmentioning
confidence: 99%
“…2 shows the comparison between results of Ref [7] and the present work for a linear foundation for time response of beam. The results show a perfect agreement with those in Ref [7], and this verifies the accuracy of presented method. Another point is that for = 1, the transverse displacement of the beam is close to be symmetrical but as the fractional order derivative used, the symmetry of the displacement is destroyed.…”
Section: Solution Of the Problemmentioning
confidence: 60%
“…Fig. 2 shows the comparison between results of Ref [7] and the present work for a linear foundation for time response of beam. The results show a perfect agreement with those in Ref [7], and this verifies the accuracy of presented method.…”
Section: Solution Of the Problemmentioning
confidence: 70%
“…Kargarnovin et al [2] used a perturbation method in conjunction with a complex Fourier transformation to study the response of infinite beams supported by nonlinear viscoelastic foundations subjected to harmonic moving loads. A. D. Senalp et al [3] investigated the dynamic response of a simply supported, finite length Euler-Bernoulli beam with uniform cross-section resting on a linear and nonlinear viscoelastic foundation subjected to a moving concentrated load and utilized the Galerkin method to solve the governing equations of motion. Ansari et al [4] used the Galerkin method and the Multiple Scales Method (MSM) to 2 Mathematical Problems in Engineering study the transverse vibration of a finite Euler-Bernoulli beam supported by nonlinear viscoelastic foundations.…”
Section: Introductionmentioning
confidence: 99%